A flexible two‐dimensional basic warranty policy with two continuous warranty regions. (9th June 2020) - Zheng, Rui; Su, Chun
Abstract: Flexible warranty policies can satisfy customers by allowing them to select the warranty regions according to their usage rates. However, customers are usually unaware of their future usage rates when they purchase a product, which makes it difficult to make sound decisions. To address the problem, this paper proposes a flexible two‐dimensional basic warranty policy with two continuous rectangular regions. Customers can gain experience of their usage rates through the first region, and thus make the second region more cost‐effective. The total price of the two subregions is equal to the basic warranty price, which is prespecified by the manufacturer. The objective is to determine the optimal boundary between the two regions from the perspective of customers. First, the learning effect is used to depict the process of gaining experience from the first region. A warranty pricing model is then developed based on the polynomial failure intensity model. On that basis, the customer's expected repair cost over the warranty period is analyzed, and a numerical method is proposed for the optimization problem. A numerical example is presented to demonstrate the effectiveness of the proposed policy. The results show that customers can benefit more from the proposed policy than from the iso‐cost warranty policy.